2009
DOI: 10.1016/j.cellsig.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Protein scaffolds in MAP kinase signalling

Abstract: The mitogen-activated protein kinase (MAPK) pathway allows cells to interpret external signals and respond in an appropriate way. Diverse cellular functions, ranging from differentiation and proliferation to migration and inflammation, are regulated by MAPK signalling. Therefore, cells have developed mechanisms by which this single pathway modulates numerous cellular responses from a wide range of activating factors. This specificity is achieved by several mechanisms, including temporal and spatial control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
164
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 87 publications
(132 reference statements)
2
164
0
1
Order By: Relevance
“…Recent studies have uncovered surprising dynamics within these complexes (Garbett and Bretscher, 2014). However, the mechanisms by which scaffolds control the ERK1/2 pathway are poorly understood (Bhattacharyya et al, 2006;Brown and Sacks, 2009;Good et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have uncovered surprising dynamics within these complexes (Garbett and Bretscher, 2014). However, the mechanisms by which scaffolds control the ERK1/2 pathway are poorly understood (Bhattacharyya et al, 2006;Brown and Sacks, 2009;Good et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP1 is a widely expressed multidomain protein regulating different aspects of cell physiology and capable of binding to distinct signalling molecules (Brown and Sacks, 2006). Emerging evidence indicates that IQGAP1 acts as a scaffold for the MAPK cascade by binding b-Raf, MEK1/2 and ERK1/2, and regulating their activation in response to EGF in fibroblasts and epithelial cells (Brown and Sacks, 2009). We recently showed that IQGAP1 also acts as a scaffold of the MAPK pathway in the heart by binding to c-Raf, MEK1/2 and ERK1/2 (Sbroggiò et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Temporal and spatial control of MAPK signaling is regulated by protein scaffolds (17,18). Two proteins, PEA-15 and SEF, have been identified as cytoplasmic anchors for ERK2 (18).…”
Section: Discussionmentioning
confidence: 99%